Globalisasi: Menindas dan Memiskinkan Masyarakat - Dheny Wiratmoko (LPPM Press, 2014)
Along with the time development, the masterpiece of human civilization will be morevisible. Constructive thoughts always colours the processes of the development. Thedevelopment of information and technology will facilitate the access to the necessitiesof life. Geographical boundaries between countries, as if it was not able to recognize, asa result, there is often increasingly complex intersection between cultures. Globalizationmakes the social order of society change. The shift of an agrarian to an industrial societyincreasingly inevitable, consequently, capital factor extremely plays role. Capitalismgrows everywhere, both in developed countries and in developing countries. Developedcountry and has a lot of capital will dominate the economic sector. As a result , fordeveloping countries , of course, will depend on the help of other countries , as a result, the new style of economic imperialism and colonialism will emerge by itself . To dealwith this, the development sector must be exactly run. The development must be felt bythe whole societies.